Engagement of International Students at Irish Higher Education Institutions - Darmody, Merike; Groarke, Sarah; Mihut, Georgiana (Journal of International Students, 2022)
Existing research paints a mixed picture of how international students fare academically following a transition to a host higher education institution. Most studies that have examined differences between domestic and international students’ engagement treated international students as a homogenous group. Less evidence is available on the experiences of international students from different regional groups. Drawing on Irish Student Engagement Survey data, this article explores the extent to which international students’ engagement differs from that of their Irish peers, and whether there are differences across regions of origin. The findings indicate that while international students are highly engaged compared to their Irish counterparts, regional differences persist when the data were disaggregated. The paper is of potential interest to policymakers and higher education institutions, offering insights into how the provision of services and supports to international students could be better targeted.